The ISoP Standards and Best Practices Committee. Issue 6 (12th March 2014) - Bruno, R; Mentré, F; Tannenbaum, S; Wang, Y; Corrigan, B; Mager, D E
<x xml:space="preserve">Abstract</x> The mission of the International Society of Pharmacometrics (ISoP) Standards and Best Practices Committee is to provide best practices and recommendations for standard pharmacometric analyses—e.g., population pharmacokinetics/pharmacodynamics (PK/PD), exposure–response, disease models—with the goal of increasing consistency, productivity, quality, communication, and impact of pharmacometrics on decision making. We present the progress and plans of the committee and call for volunteers to start new initiatives. Clinical Pharmacology & Therapeutics (2014); 95 6, 581–582. doi:10.1038/clpt.2014.65